New Transform Fundamental Properties and Its Applications - K. Jabber, Alaa; Naji Mohammed Tawfiq, Luma (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this paper, new transform with fundamental properties are presented. The new transform has many interesting properties and applications which make it rival to other transforms.Furthermore, we generalize all existing differentiation, integration, and convolution theorems in the existing literature. New results and new shifting theorems are introduced. Finally, comprehensive list of this transforms of functions will be providing.